Pengaruh Penggunaan Media Sosial Instagram Bagi Mahasiswa STMIK Borneo Internasional Balikpapan Menggunakan Technology Acceptance Model (TAM) - Ego Ismawan; Dila Seltika Canta; Elvin Leander Hadisaputro (STMIK Budi Darma, 2022)
Instagram is one of the most popular social media applications in Indonesia and in the world and almost all people access it. The word Instagram is a combination of Insta (instant) and telegram. Insta refers to a polaroid camera that can produce photos instantly. Through Instagram we can upload photos and videos, and publish them. The purpose of this study was to analyze the factors of the technology acceptance model related to the use of Instagram at STMIK Borneo International Balikpapan. The problems that exist in this study are the ease of using the system, the use of the system, and the attitude it causes. This type of research is a case study. The subjects in this study were active students at STMIK Borneo Internasional class 2018-2020 who had been actively using Instagram for the last 5 months. The technique used for data collection in this research is a survey method, and by using a questionnaire. The software used by researchers to analyze the research data is IBM SPSS 25. From the research results, users feel that it is easy to use Instagram social media, and users feel the benefits of Instagram social media. From the convenience and also the benefits felt by users, the interest in using Instagram social media also produces a very good response. Based on data analysis, Perceived usefulness (POU) has a positive and significant effect on behavior intention (BEU) using Instagram. The t-statistic value is 5.040 > 2.032 with a stg value of 0.000 < 0.05. Perceived ease of use (PEU) has a positive and significant effect on behavior intention (BEU) using Instagram. The t-statistic value is 3.903 > 2.032 with a stg value of 0.000 < 0.05. In other words, the ease and benefits obtained are one of the factors in increasing interest in using Instagram social media.